1995
DOI: 10.1103/physreve.52.r1269
|View full text |Cite
|
Sign up to set email alerts
|

Unusual universality of branching interfaces in random media

Abstract: We study the criticality of a Potts interface by introducing a froth model which, unlike its SOS Ising counterpart, incorporates bubbles of different phases. The interface is fractal at the phase transition of a pure system. However, a position space approximation suggests that the probability of loop formation vanishes marginally at a transition dominated by strong random bond disorder. This implies a linear critical interface, and provides a mechanism for the conjectured equivalence of critical random Potts … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
88
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(95 citation statements)
references
References 17 publications
7
88
0
Order By: Relevance
“…This is based on numerical results on the random Ising model [22][23][24], the Ashkin-Teller model and the four-state Potts model [7] † (all of which exhibit continuous transitions in the absence of randomness), and the 8-state Potts model (which is first-order in its pure version.) It is backed up by the interface arguments of Kardar et al [8], which suggest that the Widom exponent for the random q-state Potts model is independent of q for sufficiently large q. (A similar lack of dependence on q has been argued for in the case of random Potts spin chains [26]; however, their critical behaviour is rather different in nature from that of the present case.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…This is based on numerical results on the random Ising model [22][23][24], the Ashkin-Teller model and the four-state Potts model [7] † (all of which exhibit continuous transitions in the absence of randomness), and the 8-state Potts model (which is first-order in its pure version.) It is backed up by the interface arguments of Kardar et al [8], which suggest that the Widom exponent for the random q-state Potts model is independent of q for sufficiently large q. (A similar lack of dependence on q has been argued for in the case of random Potts spin chains [26]; however, their critical behaviour is rather different in nature from that of the present case.…”
supporting
confidence: 70%
“…Monte Carlo work of Chen et al [6] on the q = 8 state Potts model and of Domany and Wiseman [7] on the Ashkin-Teller and four-state Potts models supports this conclusion, and goes further: the continuous transition found by these workers exhibits critical exponents which are consistent with those of the pure Ising model, namely γ /ν ≈ 1.75, β/ν ≈ 0.125 and α ≈ 0. An argument explaining these findings has been put forward by Kardar et al [8]. They study the properties of an J Cardy interface in the q-state random-bond Potts model at low temperatures.…”
mentioning
confidence: 97%
“…It has been conjectured [16] that critical random Potts models are equivalent to Ising models. Kardar et al [17] suggested a possible mechanism for this effect. Their position space renormalization group approximation suggests that the probability of loop formation in the fractal interface of the clean system vanishes marginally at a transition dominated by random bonds.…”
mentioning
confidence: 99%
“…Their results are in excellent agreement (up to q = 4) with the theoretical predictions, in the vicinity of q = 2, originally of Ludwig [19] and improved by Dotsenko et al [16]. Thus, the study of Cardy and Jacobsen [13] has resolved and critically discussed the controversy related to the early simplifying prediction from the numerical simulations on the q = 8 RBPM, that the emerging second-order phase transitions may exhibit critical exponents consistent with those of the pure Ising (q = 2) model [11,12].…”
Section: Introductionmentioning
confidence: 82%